DEVELOPING STUDENTS’ SPEAKING COMPETENCE THROUGH ROLE PLAYS - Munavvar Bektemirova; Mahbuba Holmatova (Web of Journals Publishing, 2025)
This article explores the use of role plays as an effective strategy for developing students’ speaking competence in language learning. Speaking is a crucial skill in language acquisition, yet many students struggle with fluency, confidence, and communicative effectiveness. Role-playing activities provide a structured yet flexible environment where students can practice real-life communication, engage in meaningful dialogues, and enhance their interaction skills. The article reviews relevant literature on role plays in language teaching, presents sample role-play activities, and discusses their benefits in fostering speaking proficiency.
Keywords: Speaking competence, role play, language learning, communicative approach, fluency, interactive learning.